Can edible mushrooms boost soil health in banana organic systems? - Ocimati, Walter; Were, Evans M.; Ogwal, Geofrey; Dita Rodriguez, Miguel Angel; Tazuba, Anthony Fredrick Kadama; Zheng, Sijun; Blomme, Guy (International Society for Horticultural Science, 2023)
Manipulation of the rhizosphere can improve soil health; and foster sustainable management of pests and diseases. Biological inputs such as spent substrates from edible mushrooms (e.g., Pleurotus ostreatus) gardens offer sustainable alternatives on that direction. This work presents a meta-analysis of major trends in knowledge generation on edible mushroom use in agriculture, especially to benefit the crop rhizosphere. It further delves into a detailed synthesis of the effects of spent mushroom wastes (SMW) on the physical, chemical, and biological properties of the soil rhizosphere and agroecosystems. The review concludes by providing an outlook on how SMW can potentially support the management of key soil health challenges in organic banana production systems.